Adding Some Green to the Greening: Improving the EU's Ecological Focus Areas for Biodiversity and Farmers. Issue 5 (6th January 2017) - Pe'er, Guy; Zinngrebe, Yves; Hauck, Jennifer; Schindler, Stefan; Dittrich, Andreas; Zingg, Silvia; Tscharntke, Teja; Oppermann, Rainer; Sutcliffe, Laura M.E.; Sirami, Clélia; Schmidt, Jenny; Hoyer, Christian; et al.
Abstract: Ecological Focus Areas (EFAs) are one of the three new greening measures of the European Common Agricultural Policy (CAP). We used an interdisciplinary and European‐scale approach to evaluate ecological effectiveness and farmers' perception of the different EFA options. We assessed potential benefits of EFA options for biodiversity using a survey among 88 ecologists from 17 European countries. We further analyzed data on EFA uptake at the EU level and in eight EU Member States, and reviewed socio‐economic factors influencing farmers' decisions. We then identified possible ways to improve EFAs. Ecologists scored field margins, buffer strips, fallow land, and landscape features as most beneficial whereas farmers mostly implemented "catch crops and green cover, " nitrogen‐fixing crops, and fallow land. Based on the expert inputs and a review of the factors influencing farmers' decisions, we suggest that EFA implementation could be improved by (a) prioritizing EFA options that promote biodiversity (e.g., reducing the weight or even excluding ineffective options); (b) reducing administrative constraints; (c) setting stricter management requirements (e.g., limiting agrochemical use); and (d) offering further incentives for expanding options like landscape features and buffer strips. We finally propose further improvements at the next CAP reform, to improve ecological effectiveness and cost‐effectiveness.